TI_GERICHTE 12.2016.218 vom 14. Juni 2017 , Riconoscimento ed exequatur - decreto ingiuntivo italiano ex art. 647 CPCIt - TI Tribunale d'appello (2017)
Riconoscimento ed exequatur - decreto ingiuntivo italiano ex art. 647 CPCIt